Insects That Feed on Faba Bean in Southern Florida - Gregg S. Nuessly; M. G. Hentz; Robert Beiriger; B. T. Skully; Susan E. Halbert; Michael C. Thomas; Lionel A. Stange; Glavis B. Edwards; John B. Heppner; Gregg S. Hodges; Gary J. Steck (EDIS)
The information provided in this document is the result of a two-year study to document insects and insect-transmitted diseases that may have to be considered as pests to this potential crop for Florida (Figure 1). This list of plant and insect feeders will also serve as a reference to help growers, scouts and home gardeners determine which insects they may find on faba beans. This document is ENY-703, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2005.